Waste Management and the Circular Economy in Cyprus—The Case of the SWAN Project - Angelis-Dimakis, Athanasios; Arampatzis, George; Alexopoulos, Andreas; Pantazopoulos, Andreas; Vyrides, Ioannis; Chourdakis, Nikolaos; Angelis, Vasilis (My University, 2022)
The increase in waste volume and greenhouse gas emissions and decrease in raw-material reserves are some of the serious problems that our planet is facing. The measures needed to address these issues cannot be implemented under the prevailing linear economy model; hence, the circular economy model has been introduced. The successful implementation of circularity, whose basic principles include waste reduction, reuse, and recycling, requires a change in the behaviour of all the parties involved and is expected to lead to industrial–urban symbiosis schemes. The present paper looks at the current state and future prospects of the circular economy in Cyprus, based on the evidence drawn from an EU-funded project entitled “a digital Solid Waste reuse plAtform for BalkaN” (Project Acronym: SWAN). The project’s main objective was the design and development of a digital solid waste reuse platform involving four countries: Greece, Albania, Bulgaria, and Cyprus. Using the data collected, in the context of this project, from a sample of Cypriot industries, we looked into the familiarisation of the respondents with the basic concepts of circularity and their willingness to participate in symbiotic value chains. Moreover, we examined the composition of the waste streams produced by those industries and proposed potential waste reuse business models and subsequent symbiotic clusters.
Keywords: Circular economy; Cyprus; Industrial symbiosis; Solid waste; SWAN project; Waste management